Technology acceptance model (TAM) of telescreening innovation for the prevention of mortality of high-risk pregnant women in Jayapura Regency, Papua - Kurniawan, Adi; Farabi, M.J. Al (Science Midwifery, 2024)
The maternal mortality rate in Papua is still high. This study aimed to assess the readiness and benefits of telescreening high-risk pregnant women based on the Technology Acceptance Model (TAM) theory in Jayapura District, Papua. This cross-sectional study was based on the Technology Acceptance Model (TAM) questionnaire distributed to health workers with a validated Likert scale, and analyzed using the Structural Equation Model with the LISREL application. The results of the analysis showed that the total internet connection was 71% good or very good. 77% of respondents felt that telescreening high-risk pregnant women would be useful with 76% of respondents having the intention to commit to using the telescreening. Internet access in Jayapura Regency is good and not a barrier to telescreening. This TAM can be the basis for developing telescreening for early detection of high-risk pregnant women, so that deaths can be prevented